2018
DOI: 10.1155/2018/5243105
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Abdominal Hemorrhage following Cardiopulmonary Resuscitation: A Report of Two Cases

Abstract: Cardiopulmonary resuscitation (CPR) represents an emergency procedure, consisting of chest compressions and artificial ventilation. Two rare cases of intra-abdominal bleeding following cardiac compressions are reported. The first case was a 29-year-old female with massive pulmonary embolism (PE). Following CPR due to cardiac arrest, she showed signs of intra-abdominal bleeding. A liver laceration was found and sutured. The patient passed away, due to massive PE. The second patient was a 62-year-old female, suf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Potentially lethal complications to abdominal organ such as laceration of liver, spleen and stomach were also reported at the recommended compression site 15 , 16 . However, it appears that there have been few case reports of intraabdominal organ injury during CPR, despite the fact that a significant portion of the liver and stomach is positioned in the lower region of the sternum 17 , 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Potentially lethal complications to abdominal organ such as laceration of liver, spleen and stomach were also reported at the recommended compression site 15 , 16 . However, it appears that there have been few case reports of intraabdominal organ injury during CPR, despite the fact that a significant portion of the liver and stomach is positioned in the lower region of the sternum 17 , 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Primary pneumoperitoneum after CPR results from perforations of the gastrointestinal tract, most commonly the esophagus and stomach [8] . During CPR, air can track from the esophagus to the stomach secondary to chest compressions or ventilation, increasing gastric pressure causing mucosal tears or, more rarely, perforation [9] . In most cases, perforations occur in the lesser curvature of the stomach near the gastro-esophageal junction.…”
Section: Discussionmentioning
confidence: 99%
“…Koutserimpas et al reported two cases of hemoperitoneum following CPR. 10 The first included a 29-year-old female who had a massive pulmonary embolism and developed left hepatic lobe laceration (5 cm) because of CPR. The second patient was a 62-year-old female that developed cardiac arrest after drowning.…”
Section: Discussionmentioning
confidence: 99%